Pengaruh Model Pembelajaran Discovery Learning Berbantuan Media Flipbook Terhadap Pemahaman Konsep Siswa Pada Materi Wujud Zat dan Perubahannya Kelas IV SD Negeri 34 Pangkalpinang - Mutiara Putrihomsa; Erika Fitri Wardani; Feri Ardiansah (Universitas Muhammadiyah Bangka Belitung, 2026)
This research is conducted due to the low level of student learning outcomes. It shows that 82.05% of students have not reached the KKTP (Preparatory Competency Level). The learning process is still predominantly dominated by conventional instructional methods and limited variations of learning media, such as lectures, printed textbooks, and whiteboards. Therefore, this study aims to examine the effect of the discovery learning model assisted by flipbook-based media on students’ conceptual understanding of the topic of states of matter and their changes among fourth-grade students at SD Negeri 34 Pangkalpinang. This study employed a quantitative, pre-experimental design, specifically a one-group pretest–posttest design. The sample consisted of all fourth-grade students at SD Negeri 34 Pangkalpinang, totalling 39 students, and was selected using a total sampling technique. Data were analysed using the Shapiro–Wilk test for normality, followed by a paired-sample t-test. Based on the research findings, the normality test indicated that the pretest data had a significance value of 0.114 (> 0.05) and the posttest data had a significance value of 0.140 (> 0.05), indicating that both datasets were normally distributed. The results of the hypothesis testing using a paired-sample t-test revealed a significant difference between the pretest and posttest scores (p = 0.000 < 0.05), with the posttest scores being significantly higher than the pretest scores. Therefore, the alternative hypothesis (Hₐ) was accepted. It can be concluded that the discovery learning model assisted by flipbook media has a significant effect on students’ conceptual understanding of the topic of states of matter and their changes among fourth-grade students at SD Negeri 34 Pangkalpinang.